The effect of experiential quality, experiential value and image in increasing experiential satisfaction and revisit intention - Herru Sugandi; Vidyarini Dwita (Marketing Management Studies, 2022)
The purpose of this study was to analyze the effect of experiential quality, experiential value and image in increasing experiential satisfaction and revisit intention at the ABG Lubuk Minturun Swimming Pool. The population in this study were all people who had visited the ABG Lubuk Minturun Swimming Pool, the number of which was not known with certainty. While the number of samples in this study amounted to 170 respondents using purposive sampling method. The analytical technique used is SEM analysis using smart PLS3. The results of the study are (1) There is a significant effect between experiential quality and experiential satisfaction. (2) There is no significant effect between experiential value and experiential satisfaction. (3) There is a significant and positive effect between image and experiential satisfaction. (4) There is a significant and positive effect between experiential satisfaction and revisit intention. (5) There is a significant and positive effect between experiential quality and revisit intention. (6) There is a significant and positive effect between experiential value and revisit intention. (7) There is no significant effect between image and revisit intention.